1994
DOI: 10.1080/01688639408402653
|View full text |Cite
|
Sign up to set email alerts
|

Is there a sex difference in human laterality? I. an exhaustive survey of auditory laterality studies from six neuropsychology journals

Abstract: The entire contents of six neuropsychology journals (98 volumes, 368 issues) were screened to identify auditory laterality experiments. Of the 352 dichotic and monaural listening experiments identified, 40% provided information about sex differences. Among the 49 experiments that yielded at least one significant effect or interaction involving the sex factor, 11 outcomes met stringent criteria for sex differences in laterality. Of those 11 positive outcomes, 9 supported the hypothesis of greater hemispheric sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(50 citation statements)
references
References 43 publications
8
40
1
1
Order By: Relevance
“…Sex differences have been reported in the dichotic listening literature. However, these findings are not consistent across studies (Hiscock, Inch, Jacek, Hiscock-Kalil, & Kalil, 1994). Some studies have shown larger asymmetry in men than women (Cowell & Hugdahl, 2000;Weekes, Zaidel, & Zaidel, 1995) while others have not (Demarest & Demarest, 1981;Foundas, Corey, Hurley, & Heilman, 2006;Hiscock & MacKay, 1985).…”
Section: University Of Sheffield Ukcontrasting
confidence: 41%
See 1 more Smart Citation
“…Sex differences have been reported in the dichotic listening literature. However, these findings are not consistent across studies (Hiscock, Inch, Jacek, Hiscock-Kalil, & Kalil, 1994). Some studies have shown larger asymmetry in men than women (Cowell & Hugdahl, 2000;Weekes, Zaidel, & Zaidel, 1995) while others have not (Demarest & Demarest, 1981;Foundas, Corey, Hurley, & Heilman, 2006;Hiscock & MacKay, 1985).…”
Section: University Of Sheffield Ukcontrasting
confidence: 41%
“…Sex differences in dichotic listening, with males having a greater REA than women, have been reported in some (Cowell & Hugdahl, 2000;Weekes et al, 1995) but not all studies (Foundas et al, 2006;Hiscock et al, 1994). In the current study a significant sex difference in laterality was found only when men were compared to women at the Low-EP phase.…”
Section: Dichotic Listening and Menstrual Cycle 303mentioning
confidence: 99%
“…This advantage might arise from differences in the processing as well as the organisation of Meta-analyses, summarising several dichotic listening language in the brain. For example, multiple findings from studies indicated that women are less lateralised than man fMRI [21], dichotic listening [11] and visual laterality when processing language [11,17]. Because this could studies [12] suggest stronger lateralisation of language explain the temporal advantage of women in our data, all functions to the left hemisphere in males, whereas lansubjects were reinvited to participate in a dichotic listening guage functions in females tend to be organised more experiment.…”
Section: Dichotic Listeningmentioning
confidence: 69%
“…The right ear advantage (REA) observed in healthy, right-handed adults has been shown in some studies to be greater in men compared to women (Cowell & Hugdahl, 2000;Wadnerkar, Whiteside, & Cowell, 2008). However, this is a controversial finding which has not always been replicated (Foundas, Corey, Hurley, & Heilman, 2006;Hiscock, Inch, Jacek, Hiscock-Kalil, & Kalil, 1994). Voyer's (1996) meta-analysis showed significant yet small estimated effect sizes for male-greater-thanfemale asymmetry contrasts derived from verbal dichotic listening tests.…”
Section: Introductionmentioning
confidence: 95%